Persuasion - Austen, Jane, 1775-1817.; Helal, Kathleen (New York : Simon & Schuster Paperbacks, 2009)
Twenty-seven-year old Anne Elliot is Austen's most adult heroine. Eight years before the story proper begins, she is happily betrothed to a naval officer, Frederick Wentworth, but she precipitously breaks off the engagement when persuaded by her family.
"Includes detailed explanatory notes, an overview of key themes, and more"--Page 1 of cover.
Keywords: Rejection (Psychology) -- Fiction; Motherless families -- Fiction; Ship captains -- Fiction; Young women -- Fiction; England -- Fiction; Psychological fiction; Love stories